Effect of laser energy and pulses on size and concentration of gold nanoparticles in DDDW by LALP method - Al-Alousi, Mazin A. (Iraqi Journal of Physics, 2019)
The size and the concentration of the gold nanoparticles (GNPs)synthesized in double distilled deionized water (DDDW) have beenfound to be affected by the laser energy and the number of pulses.The absorption spectra of the nanoparticles DDDW, and thesurface plasmon resonance (SPR) peaks were measured, and found tobe located between (509 and 524)nm using the UV- Visspectrophotometer. SPR calculations, images of transmissionelectron microscope, and dynamic light scattering (DLS) methodwere used to determine the size of GNPs, which found to be rangedbetween (3.5 and 27) nm. The concentrations of GNPs in colloidalsolutions found to be ranged between (37 and 142) ppm, andmeasured by atomic absorption spectroscopy (AAS).